Potensi Usaha Kuliner Asli Daerah dalam Menunjang Pariwisata di Provinsi Bengkulu - Suswati Nasution; Rinto Noviantoro (Entrepreneurship Faculty, Universitas Garut, 2019)
This study is concerned with the potentials of indigenous culinary businesses in several tourist areas in Bengkulu. Using a descriptive approach, we look at the development of culinary industry in the research locus aiming to find out the strategies applied by local culinary entrepreneurs to introduce their indigenous culinary so as to support the regional tourism development in general. Primary research data were collected through intreviews with tourists and culinary business owners at the research locus. Secondary research data were obtained from Bengkulu Regional Adminstration Office, Bengkulu Tourism Office, and Statistics Bureau of Bengku. These data were analyzed using SWOT analysis method